(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The study aimed to measure the impact of marketing literacy on the awareness of Riyadh Season visitors regarding deception and commercial fraud at a 0.05 significance level. The independent variable is marketing literacy, while the dependent variable, visitors’ awareness, consists of three sub-variables: skills, knowledge, and situations. The population for this study includes all visitors to Riyadh Season 2025, which is expected to reach 16 million people. Data were collected using a purposive sampling technique, resulting in a sample size of 386 non-Saudi visitors. A five-point Likert scale was employed for the assessment. The results indicated that visitors’ awareness is significantly influenced by marketing situations, more so than by marketing skills and knowledge. The study found that both pre-marketing and post-marketing conditions during the Riyadh Season have a strong impact on visitors’ awareness of negative practices. Finally, the study offers several recommendations to enhance awareness among visitors, including educational market visits, strengthening supervision by authorities, activating the role of the Consumer Protection Association, and establishing a tourism court.